Strategic Reorientation in Human Capital: A Case Study of the Manufacturing Company - Czerniachowicz, Barbara (Journal of Corporate Responsibility and Leadership, 2017)
The aim of this article is to present the selected theo-retical and practical aspects of human capital and strategic reori-entation in human resources management in the manufacturing company. The organisation under the study is one of the producers of machine parts used in different industrial sectors in Poland. In order to achieve the aim of the paper, the following operational objectives have been formulated: (1) to discuss the concepts of human resources management; (2) to identify the strategic reorien-tation mainly focused on the area of employment in the manufac-turing company; (3) to assess the implementation of the changes in the HR strategy of the manufacturing company. The analysis is based on detailed interviews with the top management as well as the source materials collected from the manufacturing company.